Tata: Evolution Of A Corporate Brand - Morgen Witzel; WITZEL (Morgen); CHARAN (Ram) (Penguin Business Haryana, 2024)
A series of high-profile acquisitions, including Jaguar Land Rover and Corus Steel, together with the launch of the Nano (the world$1 (Bs first Rs. 1 Lakh/ below US$ 2500 car), is set to change our perception of India$1 (B: on the threshold of becoming a truly global brand.*s oldest and most respected corporate brand. With a major international presence, in a variety of areas including steel, tea, chemicals, communications and software, Tata now stands 65th in the world brand valuation league. But what is the Tata brand all about? What are its values? How do people perceive it, in India and around the world? In this absorbing and informed book Morgen Witzel digs into the heart of the Tata enterprise, describes its origins, how Tata$1 (Bs reputation and image evolved, and how the group has worked to transform that image into a powerful and valuable brand. Tata: The Evolution of a Corporate Brand goes to the core of the Tata ethos to explore the unique relationship between the Tata group and the Indian people, a relationship that goes beyond the achievements of a successful business to its social contributions for its employees and the society at large. Finally it asks how that reputation will be perceived and understood as Tata moves into global markets. Whether you$1 (Bre an entrepreneur, a manager, a marketer, or an interested Tata loyalist this book will help you understand the durability of the brand and inspire you with the values it holds onto in the global economy.s
Keywords: Tata Group--Public relations; Corporate image--India; Branding (Marketing)--India; Creative ability in business--India.